Isolation and identification of SiCOL5, which is involved in photoperiod response, based on the quantitative trait locus mapping of Setaria italica - Li, Fei-fei; Niu, Jia-hong; Yu, Xiao; Kong, Qing-hua; Wang, Run-feng; Qin, Ling; Chen, Er-ying; Yang, Yan-bing; Liu, Zhen-yu; Lang, Li-na; Zhang, Hua-wen; Wang, Hai-lian; et al. (Frontiers in Plant Science, 2022)
Foxtail millet (Setaria italica) is a versatile grain and fodder crop grown in arid and semi-arid regions. It is an especially important crop for combating malnutrition in certain poverty-stricken areas of the world. Photoperiod sensitivity is a major constraint to the distribution and utilization of foxtail millet germplasm resources. Foxtail millet may be suitable as a model species for studying the photoperiod sensitivity of C4 crops. However, the genetic basis of the photoperiod response of foxtail millet remains poorly studied. To detect the genetic basis of photoperiod sensitivity-related traits, a recombinant inbred line (RIL) population consisting of 313 lines derived from a cross between the spring-sown cultivar “Longgu 3” and the summer-sown cultivar “Canggu 3” was established. The RIL population was genotyped using whole-genome re-sequencing and was phenotyped in four environments. A high-density genetic linkage map was constructed with an average distance between adjacent markers of 0.69 cM. A total of 21 quantitative trait loci (QTLs) were identified by composite interval mapping, and 116 candidate genes were predicted according to gene annotations and variations between parents, among which three genes were considered important candidate genes by the integration and overall consideration of the results from gene annotation, SNP and indel analysis, cis-element analysis, and the expression pattern of different genes in different varieties, which have different photoperiod sensitivities. A putative candidate gene, SiCOL5, was isolated based on QTL mapping analysis. The expression of SiCOL5 was sensitive to photoperiod and was regulated by biological rhythm-related genes. Function analysis suggested that SiCOL5 positively regulated flowering time. Yeast two-hybrid and bimolecular fluorescence complementation assays showed that SiCOL5 was capable of interacting with SiNF-YA1 in the nucleus.